A proton enhanced transport forward osmosis membrane and its preparation method and application
Through the introduction of metal-organic frame nanoparticles in the positive osmotic membrane to form a high-efficiency proton transmission channel, the problem of low existing membrane proton transmission efficiency is solved, and the overall performance of the infiltration biochemical system is significantly improved.
Patent Information
- Application Number
- CN202111264437.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-18
- Filing Date
- 2021-10-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-10-28
AI Technical Summary
The existing positive permeability (FO) membranes have poor proton transport efficiency in the permeable bioelectrochemical system (OsBES), resulting in cathode alkalization, negative potential shift and increased reverse salt flux, affecting the system's operating efficiency.
Metal-organic framework (MOFs) nanoparticles are used as proton conduction media, and a salt-intercepting layer is formed in the forward osmosis membrane through phase inversion method and interfacial polymerization method to construct an efficient proton transmission channel.
It has significantly improved the efficiency of proton transmission, enhanced the capacity and conductivity of the membrane ion exchange, and improved the pollutant degradation efficiency, electricity production and water production of infiltration biochemical chemical systems.
Smart Images

Figure CN113975967B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation membrane materials and relates to a proton enhanced transmission forward osmosis membrane and a preparation method and application thereof. Background Art
[0002] Osmotic Bioelectrochemical System (OsBES) is a new wastewater treatment process developed in recent years. This new synergistic system combines the advantages of forward osmosis (FO) and bioelectrochemical system (BES). It not only simply degrades organic pollutants, but also can simultaneously realize the function of recycling nutrients, energy, water molecules and other components in wastewater. However, since the cathode of the osmotic bioelectrochemical system (OsBES) is easily alkalized during operation, this will not only cause the cathode potential to shift negatively, leading to an increase in the pH gradient between the positive and negative electrodes, thereby generating problems of overpotential and voltage loss, but also cause a higher reverse salt flux, polluting the wastewater to be treated, and thus affecting the overall operating efficiency of the osmotic bioelectrochemical system (OsBES).
[0003] Microorganisms in the anode chamber of the Osmotic Bioelectrochemical System (OsBES) degrade organic pollutants into carbon dioxide and other substances, while releasing a large number of protons. Therefore, if the rapid transfer of protons from the anode chamber to the cathode chamber can be achieved, it will play a vital role in alleviating cathode alkalinization. The forward osmosis (FO) membrane is a key component of the Osmotic Bioelectrochemical System (OsBES) and plays an important role in proton transport. However, the current commercial forward osmosis (FO) membrane has an unsatisfactory proton transport efficiency when used in the Osmotic Bioelectrochemical System (OsBES). Because these ordinary forward osmosis (FO) membranes only have osmotic functions and have no specific selectivity for protons, they can only migrate from the anode chamber to the cathode chamber with water molecules under the action of the osmotic pressure difference. Therefore, the current forward osmosis (FO) membrane has a far from reaching its limit in terms of proton transport efficiency, and there is still a lot of room for improvement. The market is in urgent need of developing a forward osmosis (FO) membrane that has specific selectivity for protons and contains spacious proton transfer channels inside, in order to achieve rapid transfer of protons from the anode to the cathode, thereby improving the water production and electrical decontamination effect of the osmotic bioelectrochemical system (OsBES) and achieving the maximum efficiency of the osmotic bioelectrochemical system (OsBES).
[0004] Metal-organic frameworks (MOFs) are crystals formed by self-assembly of metal ions or clusters and organic ligands through coordination bonds. Due to their high porosity, large internal specific surface area and structural adjustability, they have been widely studied and shown great application potential in related fields such as gas separation and storage, catalysis, drug delivery, ion conduction and wastewater treatment (Chemical Reviews, 2020, 120(16), pp8416–8467). As an emerging proton-conducting material, the high crystallinity and pore space of MOFs are conducive to the injection of proton-conducting media into them, showing unique molecular dynamics. Moreover, MOFs have good compatibility with membrane materials (Desalination, 2021, 500, 114867).
[0005] Therefore, it is necessary to use new metal-organic frameworks (MOFs) nanomaterials to prepare new composite forward osmosis membranes in order to improve the performance of the composite forward osmosis membranes, such as ion exchange capacity, electrical conductivity and proton transfer flux. Summary of the invention
[0006] In view of this, one of the objects of the present invention is to provide a proton enhanced transport forward osmosis membrane; a second object of the present invention is to provide a method for preparing a proton enhanced transport forward osmosis membrane; a third object of the present invention is to provide an application of a proton enhanced transport forward osmosis membrane in an osmotic bioelectrochemical system.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] 1. A method for preparing a proton enhanced transport forward osmosis membrane, the method comprising the following steps:
[0009] (1) Preparation of a self-supporting polymer-based membrane: uniformly dispersing metal organic framework nanoparticles in an organic solvent, adding a film-forming polymer, stirring to form a uniform and transparent casting solution, and pouring the casting solution onto a clean glass plate, and using a non-solvent induced phase inversion method to prepare a self-supporting polymer-based membrane with proton enhanced transport;
[0010] (2) preparing an organic phase solution and an aqueous phase solution: dissolving the metal organic framework nanoparticles and the organic phase monomer in an alkane to form an organic phase solution, and dissolving the aqueous phase monomer in water to form an aqueous phase solution;
[0011] (3) preparing a salt interception layer: soaking the self-supporting polymer base membrane obtained in step (1) in the aqueous phase solution for 1 to 10 minutes, taking it out and purging it with nitrogen to remove excess solution on the surface, and then soaking it in an organic phase solution for 1 to 150 seconds, so that the aqueous phase monomers and the organic phase monomers undergo interfacial polymerization reaction on the surface of the supporting base membrane to form a salt interception layer on the surface of the self-supporting polymer base membrane;
[0012] (4) Preparation of a self-supporting nanocomposite forward osmosis membrane: Dry the self-supporting polymer-based membrane with the salt interception layer formed on the surface in step (3) at 30 to 120° C. for 1 to 30 min to obtain a self-supporting nanocomposite forward osmosis membrane.
[0013] Preferably, the metal organic framework nanoparticles are any one of material I, material II or material III;
[0014] The material I is MIP-177-LT, PCMOF-17, CAU-1, CuBTC, FeBTC, Cu2(PZDC)(DPYG), Cu-TCPP, MIP-202(Zr), [Ni2-(d obdc)(H2O)2], MIL-47, MIL-53(Al), MIL-53(Cr), MIL-53(Fe), MIL-53(V), MIL-88, MIL-89, MIL-125, MI L-100(Cr), MIL-100(Fe), MIL-101(Cr), HKUST-1, ZnBTC, Zn3BDC·2BTC, PCN-222, CuBDC-NS, Cu(BDC), BU T-8(Cr), BUT-52, TfOH@MIL-101, Fe-CAT-5, H3PO4@MIL-101, M2(dobdc)(H2O)2, Ni-CPO-27, PCMOF10, [Fe 16 Ο4(SO4) 12 (L2)6(DMF) 24 ], [MgL(H2O)2] n , UMCM-150 or PCN-14, wherein M in M2(dobdc)(H2O)2 is any one of Mg, Mn, Fe, Co, Ni or Zn;
[0015] The material II is any one or more of the UiO series, ZIF series, UMCM series or NOTT series materials;
[0016] The material III is any one or more of the products obtained by modifying the material I and the material II with any one of the functional groups -OH, NH2-, -SO3H, -COOH, -SH or -PO3H.
[0017] Preferably, the organic solvent in step (1) is any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, m-cresol or chloroform;
[0018] The film-forming polymer is any one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polyimide, polyetherimide, polylactic acid, chitosan, polyvinyl alcohol, cellulose acetate or cellulose triacetate.
[0019] Preferably, the mass ratio of the metal organic framework nanoparticles to the organic solvent in step (1) is 0.1 to 10:100;
[0020] The mass ratio of the metal organic framework nanoparticles to the film-forming polymer is 1:1000 to 7:10.
[0021] Preferably, the conditions of the non-solvent induced phase inversion method in step (1) are: adjusting the scraper height to 40 to 350 μm, and soaking the glass plate in a coagulation bath at room temperature for 5 to 30 minutes, and the obtained self-supporting polymer base film is repeatedly washed and placed in deionized water at 4°C for storage.
[0022] Preferably, in step (2), any one or both of the organic phase monomer acyl chloride or isocyanate, the acyl chloride is any one of isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, trimesoyl chloride or pyromellitoyl chloride;
[0023] The alkane is any one or more of n-hexane, n-heptane or n-decane;
[0024] The mass ratio of the total mass of the metal organic framework nanoparticles and the organic phase monomer to the alkane is 0.01 to 6:100;
[0025] The total mass of the metal organic framework nanoparticles and the organic phase monomer is 0-1:0.01-5.
[0026] Preferably, the aqueous phase monomer in step (2) is a polyamine, and the polyamine is m-phenylenediamine;
[0027] The mass ratio of the aqueous phase monomer to water is 0.1 to 10:100.
[0028] 2. The self-supporting nanocomposite forward osmosis membrane prepared according to the above preparation method.
[0029] 3. Application of the above self-supporting nanocomposite forward osmosis membrane in osmotic bioelectrochemical system.
[0030] The beneficial effects of the present invention are as follows: in view of the good proton conductivity of the new metal organic framework nanomaterial, the present invention provides a method for preparing a proton enhanced transport forward osmosis membrane, the preparation method comprising introducing metal organic framework nanoparticles into a supporting base membrane prepared by a phase inversion method, and / or into a salt interception layer prepared by an interfacial polymerization method, respectively, to prepare a composite forward osmosis membrane with high proton transport performance. Since metal organic framework nanoparticles have ultra-high specific surface area, high porosity and easy functionalization, and have good compatibility with the membrane, they can provide additional abundant proton transport channels for the forward osmosis membrane, so the self-supporting nano composite forward osmosis membrane prepared by the present invention has excellent ion exchange capacity, electrical conductivity and proton transport flux, and its application in an osmotic bioelectrochemical system can effectively improve the pollutant degradation efficiency, power production and water production.
[0031] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0033] Figure 1 a is a surface SEM image of the self-supporting nanocomposite forward osmosis membrane prepared in Example 2, and b is a cross-sectional SEM image of the self-supporting polymer-based membrane prepared in Example 2;
[0034] Figure 2 is the surface roughness of the self-supporting nanocomposite forward osmosis membrane prepared in Example 2;
[0035] Figure 3 is the surface contact angle of the self-supporting nanocomposite forward osmosis membrane prepared in Example 2;
[0036] Figure 4 a is a cross-sectional SEM image of the self-supporting base membrane in the comparative example, and b is a surface SEM image of the self-supporting nanocomposite forward osmosis membrane in the comparative example;
[0037] Figure 5 The surface roughness of the self-supporting nanocomposite forward osmosis membrane in the comparative example;
[0038] Figure 6 is the surface contact angle of the self-supporting nanocomposite forward osmosis membrane in the comparative example. DETAILED DESCRIPTION
[0039] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and the features in the embodiments can be combined with each other without conflict.
[0040] Example 1
[0041] A proton enhanced transport forward osmosis membrane is prepared, and the specific preparation method is as follows:
[0042] 1. Disperse MIL-53 (Fe) nanoparticles uniformly in N, N-dimethylformamide (DMF) solvent at a concentration of 0.1 wt%, then add polysulfone particles (the mass concentration of the polysulfone particles after adding the polysulfone particles is 5 wt%), heat to 60 ° C and stir for 12 hours to prepare a uniform and stable mixed matrix casting solution containing MIL-53 (Fe), and let it stand for degassing for 24 hours; then pour the casting solution onto a clean glass plate, adjust the scraper height to 150 μm, scrape the film at a uniform speed, and then quickly immerse the glass plate in a pure water coagulation bath for 30 minutes, take out the formed phase inversion base membrane from the coagulation bath, and repeatedly rinse it with deionized water to obtain a self-supporting polymer base membrane with proton enhanced transmission, and place it in 4 ° C deionized water for standby use.
[0043] 2. Add 0.01 wt% of MIL-53 (Fe) nanoparticles into 0.01 wt% of trimesoyl chloride n-hexane solution and ultrasonicate for 1 h to form a uniformly dispersed organic phase solution.
[0044] 3. The above-mentioned proton-enhanced transport self-supporting polymer base membrane is immersed in a 0.1wt% aqueous solution of m-phenylenediamine for 6 minutes, taken out and purged with nitrogen to remove excess droplets on the membrane surface, and then immersed in the above-mentioned organic phase solution for 120 seconds. During this time, interfacial polymerization reaction of phenylenediamine and trimesoyl chloride occurs on the surface of the supporting base membrane to generate a salt interception layer, namely, the primary nanocomposite forward osmosis membrane is obtained.
[0045] 4. Finally, the salt-cutting layer (initial nanocomposite forward osmosis membrane) was placed in an oven at 30°C and heated for 30 minutes to obtain a self-supporting nanocomposite forward osmosis membrane with stable morphology and performance.
[0046] Example 2
[0047] A proton enhanced transport forward osmosis membrane is prepared, and the specific preparation method is as follows:
[0048] 1. Disperse Zn3BDC·2BTC nanoparticles uniformly in N,N-dimethylacetamide (DMAc) solvent at a concentration of 10wt%, then add polyethersulfone particles (the mass concentration of polyethersulfone particles after adding polyethersulfone particles is 20wt%), heat and stir for 12h, prepare a uniform and stable mixed matrix casting solution containing Zn3BDC·2BTC, and let it stand for degassing for 24h; pour the casting solution on a glass plate, adjust the scraper height to 200μm, scrape the film at a uniform speed, and then quickly immerse the glass plate in a pure water coagulation bath. After 30min, remove the formed phase inversion support base membrane from the coagulation bath and rinse it repeatedly with deionized water to obtain a self-supporting polymer base membrane with proton enhanced transmission, which is immersed in deionized water at 4°C for use.
[0049] 2. Add Zn3BDC·2BTC nanoparticles at a ratio of 0.5% (w / v) to 0.15wt% trimesoyl chloride n-hexane solution, and ultrasonicate for 1 hour to form a uniformly dispersed solution, which is the organic phase solution.
[0050] 3. Soak the self-supporting base membrane in a 10 wt% aqueous solution of m-phenylenediamine for 5 min, take it out and blow it with nitrogen to remove excess droplets on the membrane surface, and then soak it in the organic phase solution for 150 s. During this time, interfacial polymerization reaction of m-phenylenediamine and trimesoyl chloride occurs on the surface of the self-supporting base membrane to generate a salt interception layer, which is the primary nanocomposite forward osmosis membrane.
[0051] 4. Finally, the salt interception layer (initial nanocomposite forward osmosis membrane) was placed in an oven at 120° C. and heated for 10 min to obtain a self-supporting nanocomposite forward osmosis membrane with stable morphology and performance.
[0052] Example 3
[0053] A proton enhanced transport forward osmosis membrane is prepared, and the specific preparation method is as follows:
[0054] 1. Disperse Ni-CPO-27 nanoparticles uniformly in N-methylpyrrolidone (NMP) solvent at a concentration of 5 wt %, then add polyacrylonitrile particles (the mass concentration of polyacrylonitrile particles after adding the polyacrylonitrile particles is 30 wt %), heat and stir for 12 h, prepare a uniform and stable mixed matrix casting solution containing Ni-CPO-27, and let it stand for degassing for 24 h; pour the casting solution onto a clean glass plate, adjust the scraper height to 150 μm, scrape the film at a uniform speed, then quickly immerse the glass plate in a pure water coagulation bath for 30 min, take out the formed phase inversion base membrane from the coagulation bath, and repeatedly rinse it with deionized water to obtain a self-supporting polymer base membrane with proton enhanced transmission, and place it in 4° C. deionized water for standby use.
[0055] 2. Dissolve 6 wt% of phthaloyl chloride in n-hexane and ultrasonicate for 1 h to form a uniformly dispersed solution to obtain an organic phase solution.
[0056] 3. Soak the self-supporting polymer base membrane in an 8wt% aqueous solution of m-phenylenediamine for 2 minutes, take it out and blow it with nitrogen to remove excess droplets on the membrane surface, and then soak it in the organic phase solution for 100 seconds. During this time, interfacial polymerization reaction of m-phenylenediamine and phthaloyl chloride occurs on the surface of the base membrane to generate a salt interception layer, which is the primary nanocomposite forward osmosis membrane.
[0057] 4. Finally, the generated salt interception layer (initial nanocomposite forward osmosis membrane) was placed in an oven at 100° C. and heated for 8 minutes to obtain a self-supporting nanocomposite forward osmosis membrane with stable morphology and performance.
[0058] Example 4
[0059] A proton enhanced transport forward osmosis membrane is prepared, and the specific preparation method is as follows:
[0060] 1. Disperse UMCM-150-SO3H nanoparticles uniformly in dimethyl sulfoxide (DMSO) solvent at a concentration of 2.5wt%, then add polyvinylidene fluoride powder (the mass concentration of polyvinylidene fluoride powder after adding polyvinylidene fluoride powder is 25wt%), heat and stir for 12h, prepare a uniform and stable mixed matrix casting solution containing UMCM-150-SO3H, and let it stand for degassing for 24h; pour the above casting solution on a clean glass plate, adjust the scraper height to 150μm, scrape the film at a uniform speed, and then quickly immerse the glass plate in a pure water coagulation bath for 20min, take out the formed phase inversion base membrane from the coagulation bath, and repeatedly rinse it with deionized water to obtain a self-supporting polymer base membrane with proton enhanced transmission, and place it in 4℃ deionized water for standby use.
[0061] 2. Dissolve 0.3 wt% of isophthaloyl chloride in n-hexane solution to prepare an organic phase solution.
[0062] 3. Soak the above-mentioned base membrane in a 2wt% aqueous solution of m-phenylenediamine for 5 minutes, take it out and blow it with nitrogen to remove excess droplets on the membrane surface, and then soak it in the above-mentioned organic phase solution for 30 seconds. During this time, interfacial polymerization reaction of phenylenediamine and isophthaloyl chloride occurs on the surface of the base membrane to form a salt interception layer, which is the initial composite forward osmosis membrane.
[0063] 4. Finally, the generated salt interception layer (initial composite forward osmosis membrane) was placed in an oven at 50° C. and heated for 15 minutes to obtain a supported nano-composite forward osmosis membrane with stable morphology and performance.
[0064] Example 5
[0065] A proton enhanced transport forward osmosis membrane is prepared, and the specific preparation method is as follows:
[0066] 1. Disperse MIL-101(Cr)-COOH nanoparticles uniformly in N-methylpyrrolidone (NMP) solvent at a concentration of 7.5wt%, then add polyimide powder at a mass concentration of 12wt%, heat and stir for 12h, prepare a uniform and stable mixed matrix casting solution containing MIL-101(Cr)-COOH, and let it stand for degassing for 24h; pour the casting solution onto a clean glass plate, adjust the scraper height to 150μm, scrape the film at a uniform speed, then quickly immerse the glass plate in a pure water coagulation bath for 20min, take out the formed phase inversion support base membrane from the coagulation bath, and repeatedly rinse it with deionized water to obtain a self-supporting polymer base membrane with proton enhanced transmission, and place it in 4℃ deionized water for standby use.
[0067] 2. Add MIL-101(Cr)-COOH nanoparticles at a ratio of 0.3% (w / v) to 0.15wt% terephthaloyl chloride n-hexane solution, and ultrasonicate for 1 hour to form a uniformly dispersed solution, which is the organic phase solution.
[0068] 3. Soak the above-mentioned supporting base membrane in a 5wt% aqueous solution of m-phenylenediamine for 8 minutes, take it out and blow it with nitrogen to remove excess droplets on the membrane surface, and then soak it in the above-mentioned organic phase solution for 10 seconds. At this time, terephthaloyl chloride and m-phenylenediamine undergo interfacial polymerization reaction on the surface of the supporting base membrane to form a salt interception layer, which is the primary nano-composite forward osmosis membrane.
[0069] 4. Finally, the salt interception layer (initial nanocomposite forward osmosis membrane) was placed in an oven at 90° C. and heated for 12 minutes to obtain a self-supporting nanocomposite forward osmosis membrane with stable morphology and performance.
[0070] Example 6
[0071] A proton enhanced transport forward osmosis membrane is prepared, and the specific preparation method is as follows:
[0072] 1. Disperse MIP-202(Zr)-OH nanoparticles uniformly in chloroform solvent at a concentration of 8wt%, then add polylactic acid particles (the mass concentration of polylactic acid particles after adding polylactic acid particles is 25wt%), heat and stir for 12h, prepare a uniform and stable mixed matrix casting solution containing MIP-202(Zr)-OH, and let it stand for degassing for 24h; pour the casting solution on a clean glass plate, adjust the scraper height to 200μm, scrape the film at a uniform speed, then quickly immerse the glass plate in a pure water coagulation bath for 30min, take out the formed phase inversion support base membrane from the coagulation bath, and repeatedly rinse it with deionized water to obtain a self-supporting polymer base membrane with proton enhanced transmission, and place it in 4℃ deionized water for standby use.
[0073] 2. Dissolve 0.25 wt% of isocyanate in n-heptane and ultrasonicate for 1 h to form a uniformly dispersed solution to obtain an organic phase solution.
[0074] 3. Soak the self-supporting polymer base membrane in a 3.4wt% aqueous solution of m-phenylenediamine for 6 minutes, take out and remove excess droplets on the membrane surface, and then soak it in the above-mentioned organic phase solution for 100 seconds. At this time, isocyanate and m-phenylenediamine undergo interfacial polymerization reaction on the surface of the base membrane to form a salt interception layer. The salt interception layer is the primary nanocomposite forward osmosis membrane.
[0075] 4. Finally, the generated salt interception layer (initial nanocomposite forward osmosis membrane) was placed in a 60°C oven and heated for 20 minutes to obtain a self-supporting nanocomposite forward osmosis membrane with stable morphology and performance.
[0076] Comparative Example
[0077] A permeable membrane is prepared, and the specific preparation method is as follows:
[0078] 1. Dissolve the polysulfone particles in N, N-dimethylacetamide (DMAc) solvent, heat and stir for 12 hours, stand and degas for 24 hours, and prepare a uniform and stable casting solution with a concentration of 20wt%; pour the casting solution on a clean glass plate, adjust the scraper height to 200μm, scrape the film at a constant speed, and then quickly immerse the glass plate in a pure water coagulation bath. After 30 minutes, take out the formed phase inversion base membrane from the coagulation bath, and rinse it repeatedly with deionized water to obtain a support base membrane and place it in 4℃ deionized water for standby use.
[0079] 2. Dissolve m-phenylenediamine in deionized water to prepare an aqueous solution with a concentration of 10 wt %, and dissolve trimesoyl chloride in n-hexane to prepare an organic solution with a concentration of 0.15 wt %.
[0080] 3. Soak the above-mentioned supporting base membrane in the aqueous solution for 5 minutes, take out and remove the excess droplets on the membrane surface, and then soak it in the organic solution for 90 seconds. During this time, interfacial polymerization reaction of phenylenediamine and trimesoyl chloride occurs on the surface of the supporting base membrane to form a salt interception layer, which is the primary ecological permeability membrane.
[0081] 4. Finally, the primary ecological permeable membrane is placed in an oven at 80°C and heated for 20 minutes to obtain a permeable membrane with stable morphology and performance.
[0082] Performance Characterization
[0083] In order to demonstrate the excellent performance of the composite forward osmosis membrane prepared by the metal organic framework novel nano-ions, the performance of the osmotic membrane prepared in the above examples and comparative examples was tested, and the test method was as follows:
[0084] (1) Study on the proton transport performance of the permeable membranes prepared in the above examples and comparative examples
[0085] Ion exchange capacity: Ion exchange capacity (IEC) refers to the milligram equivalent of sulfonic acid groups per gram of dry membrane (meq / g), which is determined by titration analysis. The test method is as follows: accurately weigh the dry membrane mass, soak the permeable membrane in 1.0M hydrochloric acid for 48 hours at room temperature, then soak the sample in 1M sodium chloride solution for 2 days, and then titrate with 0.04M standard sodium hydroxide solution, using phenolphthalein as an indicator to determine the content of hydrochloric acid. The ion exchange capacity IEC of the membrane is calculated by formula (1):
[0086]
[0087] Conductive performance: The conductivity of the permeable membrane is characterized by conductivity. First, the membrane resistance is measured by an electrochemical workstation using the AC impedance spectroscopy measurement technology, and then the membrane conductivity in the vertical direction of the membrane surface is calculated. The membrane vertical conductivity σ (S / cm) is calculated by formula (2):
[0088]
[0089] (2) Application of proton enhanced transport nanocomposite FO membrane in OsBES
[0090] Osmosis microbial fuel cells (OsMFCs) are used as the research basis. Bipolar chamber OsMFCs are used. The anode chamber contains organic wastewater raw material liquid, and the cathode chamber contains 35g / L sodium chloride draw liquid. The nanocomposite FO membrane separates the positive and negative chambers. The membrane placement direction of forward osmosis (FO) is adopted, and the two electrodes are placed on both sides of the membrane at an equal distance. The anode chamber is filled with nitrogen for a period of time to ensure an anaerobic environment. The microorganisms are derived from the bacterial solution that has been cultured stably in the laboratory for a long time. An organic wastewater storage tank is set in front of the anode chamber to replenish wastewater to the anode chamber in time. The cathode chamber is continuously aerated. The electronic balance connected to the computer records the changes in the mass of the anode liquid. The permeate water flux (J) of the forward osmosis (FO) membrane is calculated by formula (3) w , L·m -2 ·h -1, abbreviated as LMH). The titanium wire was connected to an external resistor with a resistance of 1000Ω. After the OsMFCs were operated for a period of time, the open circuit voltage, maximum power density and current density, the pH changes of the anode and cathode chambers over time, the water flux of the nanocomposite FO membrane over time, and the removal rate of chemical oxygen demand (COD) in the wastewater were investigated. By investigating the change law of the above physical quantities, the influence of nanocomposite forward osmosis (FO) membranes with different loading amounts of metal-organic frameworks (MOFs) on the degradation efficiency, water production and power generation performance of organic wastewater in OsMFCs was established, thereby establishing the relationship between the proton transport performance in the nanocomposite forward osmosis (FO) membrane and the degradation efficiency, water production and power generation performance of organic wastewater in OsMFCs.
[0091]
[0092] Wherein, Δm(g) is the mass of pure water that permeates from the raw liquid into the drawn liquid within the time Δt(h); A m (m 2 ) is the effective membrane area;
[0093]
[0094] COD0 is the initial COD (mg) of the wastewater to be treated, COD t is the COD (mg) of the anolyte when OsMFCs are running at time t (h).
[0095] The proton transport performance of the permeable membrane prepared in the examples and comparative examples obtained by the above method is shown in Table 1:
[0096] Table 1 Proton transport performance of permeable membranes prepared in Examples and Comparative Examples
[0097] performance Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Comparative Example IEC / meq / g 1.78 3.12 2.01 1.98 2.68 2.36 0.1 σ / S / cm 0.07 0.23 0.08 0.09 0.19 0.17 0.04 Water flux / LMH 3.95 8.53 9.85 11.23 13.45 10.56 6.24 Open circuit voltage / mV 833 878 823 839 868 808 788 <![CDATA[Maximum power density / W / m 3 > 5.06 6.72 6.03 6.98 6.35 6.02 3.86 <![CDATA[Average current density / A / m 3 > 4.63 5.16 5.06 6.12 5.68 5.14 4.01 COD removal rate 76% 82% 79% 87% 88% 85% 74% pH increase by units 3.48 5.98 3.03 2.06 2.43 2.26 5.65
[0098] Where IEC is the ion exchange capacity of the nanocomposite forward osmosis membrane, σ is the electrical conductivity, water flux is the average osmotic driven water flux measured after the forward osmosis membrane is applied to OsMFCs, and pH change is the cathode liquid pH after 33 h of operation.
[0099] From the test results in Table 1, it can be seen that, compared with the comparative examples, in Examples 1 to 6 of the present invention, different types and contents of metal organic framework nanoparticles are loaded on the supporting base membrane and / or the salt interception layer to construct a continuous proton transmission channel, thereby preparing a nanocomposite forward osmosis (FO) membrane with proton enhanced transmission function. By evaluating the comprehensive performance of the forward osmosis (FO) membrane, the nanocomposite forward osmosis (FO) membrane prepared by the present invention has better ion exchange capacity and conductivity than ordinary forward osmosis (FO) membranes; and after applying it to osmotic microbial fuel cells, the power production, water production and organic wastewater degradation efficiency are also increased.
[0100] Figure 1 a is a surface SEM image of the self-supporting nanocomposite forward osmosis membrane prepared in Example 2, and b is a cross-sectional SEM image of the self-supporting polymer-based membrane prepared in Example 2; Figure 2 is the surface roughness of the self-supporting nanocomposite forward osmosis membrane prepared in Example 2; Figure 3 is the surface contact angle of the self-supporting nanocomposite forward osmosis membrane prepared in Example 2; Figure 4 a is a cross-sectional SEM image of the self-supporting base membrane in the comparative example, and b is a surface SEM image of the self-supporting nanocomposite forward osmosis membrane in the comparative example; Figure 5 The surface roughness of the self-supporting nanocomposite forward osmosis membrane in the comparative example; Figure 6 is the surface contact angle of the self-supporting nanocomposite forward osmosis membrane in the comparative example. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 It can be seen from the comparison results that, compared with the comparative example, the self-supporting base membrane prepared in Example 2 has better pore permeability, increased surface roughness, and enhanced hydrophilicity. These changes in properties can provide more abundant transmission channels for protons, reduce proton transmission resistance, and accelerate proton transmission.
[0101] Similarly, the metal organic framework nanoparticles in the above embodiments are replaced by MIP-177-LT, PCMOF-17, CAU-1, CuBTC, FeBTC, Cu2(PZDC)(DPYG), Cu-TCPP, MIP-202(Zr), [Ni2-(dobdc)(H2O)2], MIL-47, MIL-53(Al), MIL-53(Cr), MIL-53(Fe), MIL-53(V), MIL-88, MIL-89, M IL-125, MIL-100(Cr), MIL-100(Fe), MIL-101(Cr), HKUST-1, ZnBTC, Zn3BDC·2BTC, PCN-222, CuBDC-NS, Cu(BDC ), BUT-8(Cr), BUT-52, TfOH@MIL-101, Fe-CAT-5, H3PO4@MIL-101, M2(dobdc)(H2O)2, Ni-CPO-27, PCMOF10, [Fe 16 Ο4(SO4) 12 (L2)6(DMF) 24 ], [MgL(H2O)2] n, UMCM-150 or PCN-14, wherein M in M2(dobdc)(H2O)2 is any one of Mg, Mn, Fe, Co, Ni or Zn, or any one or more of UiO series, ZIF series, UMCM series or NOTT series materials, or any one or more of the products modified with any one of the functional groups of -OH, NH2-, -SO3H, -COOH, -SH or -PO3H of the above materials can improve the performance of the prepared composite forward osmosis membrane; in addition, the organic solvent used in the embodiment can be any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, m-cresol or chloroform, and the film-forming polymer can be any one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polyimide, polyetherimide, polylactic acid, chitosan, polyvinyl alcohol, cellulose acetate or cellulose triacetate. During the preparation process, the mass ratio of metal organic framework nanoparticles to film-forming polymers was 1:1000 to 7:10, and the prepared composite forward osmosis membrane was subjected to performance testing. The results showed that the nanocomposite forward osmosis (FO) membrane prepared by the present invention had superior ion exchange capacity and electrical conductivity than ordinary forward osmosis (FO) membranes; and after being applied to osmotic microbial fuel cells, the power production, water production and organic wastewater degradation efficiency were also increased.
[0102] In summary, in view of the good proton conductivity of the new metal organic framework nanomaterials, the present invention provides a method for preparing a proton enhanced transport forward osmosis membrane, the preparation method comprising introducing metal organic framework nanoparticles into a supporting base membrane prepared by a phase inversion method, and / or into a salt interception layer prepared by an interfacial polymerization method, respectively, to obtain a composite forward osmosis membrane with high proton transport performance. Since metal organic framework nanoparticles have ultra-high specific surface area, high porosity and easy functionalization, and have good compatibility with the membrane, they can provide additional abundant proton transport channels for the forward osmosis membrane. Therefore, the self-supporting nanocomposite forward osmosis membrane prepared by the present invention has excellent ion exchange capacity, electrical conductivity and proton transport flux. When applied to an osmotic bioelectrochemical system, the pollutant degradation efficiency, electricity production and water production can be effectively improved.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a proton enhanced transport forward osmosis membrane, characterized in that: The preparation method comprises the following steps: (1) Preparation of self-supporting polymer-based membranes: metal organic framework nanoparticles are uniformly dispersed in an organic solvent, a film-forming polymer is added, and the mixture is stirred to form a uniform and transparent casting solution, and the casting solution is poured onto a clean glass plate. A self-supporting polymer-based membrane with proton-enhanced transport is prepared by a non-solvent-induced phase inversion method; (2) preparing an organic phase solution and an aqueous phase solution: dissolving the metal organic framework nanoparticles and the organic phase monomer in an alkane to form an organic phase solution, and dissolving the aqueous phase monomer in water to form an aqueous phase solution; (3) Preparing a salt interception layer: soaking the self-supporting polymer base membrane prepared in step (1) in the aqueous phase solution for 1 to 10 minutes, taking it out and purging it with nitrogen to remove excess solution on the surface, and then soaking it in an organic phase solution for 1 to 150 seconds, so that the aqueous phase monomers and the organic phase monomers undergo interfacial polymerization reaction on the surface of the supporting base membrane to form a salt interception layer on the surface of the self-supporting polymer base membrane; (4) preparing a self-supporting nanocomposite forward osmosis membrane: drying the self-supporting polymer-based membrane with the salt interception layer formed on the surface in step (3) at 30-120° C. for 1-30 min to obtain a self-supporting nanocomposite forward osmosis membrane; In step (1), the mass ratio of the metal organic framework nanoparticles to the organic solvent is 0.1 to 10:100, and the mass ratio of the metal organic framework nanoparticles to the film-forming polymer is 1:1000 to 7:
10.
2. The preparation method according to claim 1, characterized in that: The metal organic framework nanoparticles are any one of material I, material II or material III; The material I is MIP-177-LT, PCMOF-17, CAU-1, CuBTC, FeBTC, Cu2(PZDC)(DPYG), Cu−TCPP, MIP-202(Zr), [Ni2-(dobdc)(H2O)2], MIL-47, MIL-53 (Al), MIL-53 (Cr), MIL-53 (Fe), MIL-53 (V), MIL-88, MIL-89, MIL-125, MIL-100(Cr), MIL-100(Fe), MIL-101(Cr), HKUST-1, ZnBTC, Zn3BDC·2BTC, PCN-222, CuBDC -NS, Cu(BDC), BUT-8(Cr), BUT-52, TfOH@MIL-101, Fe-CAT-5, H3PO4@MIL-101, M2(dobdc)(H2O)2, Ni-CPO-27, PCMOF10, [Fe 16 Ο4(SO4) 12 (L2)6(DMF) 24 ], [MgL(H2O)2] n , UMCM-150 or PCN-14, wherein M in M2(dobdc)(H2O)2 is any one of Mg, Mn, Fe, Co, Ni or Zn; The material II is any one or more of the UiO series, ZIF series, UMCM series or NOTT series materials; The material III is any one or more of the products obtained by modifying the material I and the material II with any one of the functional groups -OH, NH2-, -SO3H, -COOH, -SH or -PO3H.
3. The preparation method according to claim 1, characterized in that: The organic solvent in step (1) is any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, m-cresol or chloroform; The film-forming polymer is any one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, polyimide, polyetherimide, polylactic acid, chitosan, polyvinyl alcohol, cellulose acetate or cellulose triacetate.
4. The preparation method according to claim 1, characterized in that: The conditions of the non-solvent induced phase inversion method in step (1) are as follows: adjusting the scraper height to 40-350 μm, and immersing the glass plate in a coagulation bath at room temperature for 5-30 min. The obtained self-supporting polymer base film is repeatedly washed and stored in deionized water at 4°C for later use.
5. The preparation method according to claim 1, characterized in that: In step (2), the organic phase monomer is any one or both of an acyl chloride and an isocyanate, and the acyl chloride is any one of isophthaloyl chloride, terephthaloyl chloride, phthaloyl chloride, trimesoyl chloride or pyromellitoyl chloride; The alkane is any one or more of n-hexane, n-heptane or n-decane; The mass ratio of the total mass of the metal organic framework nanoparticles and the organic phase monomer to the alkane is 0.01 to 6:
100.
6. The preparation method according to claim 1, characterized in that: In step (2), the aqueous phase monomer is a polyamine, and the polyamine is m-phenylenediamine; The mass ratio of the aqueous phase monomer to water is 0.1 to 10:
100.
7. A self-supporting nanocomposite forward osmosis membrane prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the self-supporting nanocomposite forward osmosis membrane according to claim 7 in an osmotic bioelectrochemical system.
Citation Information
Patent Citations
Composite forward osmosis membrane with proton exchange function as well as preparation method and application thereof
CN107913600A
Separation membrane for water treatment and method for manufacturing the same
KR1020150051137A